Thermal ionization energy of hydrogen-like impurities in semiconductor materials - Poklonski, Nikolai A.; Vyrko, Sergey A.; Dzeraviaha, Aliaksandr N. (Journal of the Belarusian State University. Physics, 2020)
In the work the dependence of the thermal ionization energy of hydrogen-like donors and acceptors on their concentration in n- and p-type semiconductors is analyzed analytically and numerically. The impurity concentrations and temperatures at which the semiconductors are on the insulator side of the concentration insulator – metal phase transition (Mott transition) are considered. It is assumed that impurities in the crystal are distributed randomly (according to Poisson), and their energy levels are distributed normally (according to Gauss). In the quasi-classical approximation, it is shown, for the first time, that the decrease in the ionization energy of impurities mainly occurs due to the joint manifestation of two reasons. Firstly, from the excited states of electrically neutral impurities, a quasicontinuous band of allowed energy values is formed for c-band electrons in an n-type crystal (or for v-band holes in a p-type crystal). This reduces the energy required for the thermally activated transition of electron from the donor to the c-band (for the transition of the hole from the acceptor to the v-band). Secondly, from the ground (unexcited) states of impurities a classical impurity band is formed, the width of which at low temperatures is determined only by the concentration of impurity ions. In moderately compensated semiconductors (when the ratio of the concentration of minority impurities to the concentration of majority impurities is less than 50 %) the Fermi level is located closer to the edge of the band of allowed energy values than the middle of the impurity band, that issue reduces thermal ionization energy of impurities from states in the vicinity of the Fermi level (transition of electron from a donor to the c-band, or hole from an acceptor to the v-band). Previously, these two causes of decrease in the thermal ionization energy due to increase in the concentration of impurities were considered separately. The results of calculations according to the proposed formulas are quantitatively agree with the known experimental data for a number of semiconductor materials (germanium, silicon, diamond, gallium arsenide and phosphide, silicon carbide, zinc selenide) with a moderate compensation ratio.